PELATIHAN JARINGAN KOMPUTER UNTUK SISWA-SISWI PKL DI YPAIS FOUNDATION - Jupron; Yuda Permadi; Sarman (Abdi Jurnal Publikasi, 2025)
The digital era has created a greater need for technological innovation, with the development of technologies such as the Internet of Things (IoT), artificial intelligence (AI), and 5G networks that rely on computer networks to support advanced functionality. Computer networks play a crucial role in various sectors, including business, healthcare, and education, by improving communication, collaboration, and efficiency. The computer network training program implemented at YPAIS Foundation aims to provide basic knowledge and skills to street vendor students regarding computer networks, from introduction to the practice of making network cables and LAN configurations. This training is expected to help students develop their ability to manage and utilize computer networks, especially in the creation and management of school websites as a medium of communication and information between schools and the community. In addition, this activity also aims to provide an understanding of various types of computer networks, such as LAN, MAN, VPN, and WAN, which can be adjusted to the needs of the organization or school environment. With this training, it is hoped that the participants can improve their skills in information technology, support the development of human resources at YPAIS Foundation, and expand the use of digital technology in the current information era.